Cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10 as well as preparation method and brazing method of cobalt-based brazing filler metal
By designing a cobalt-based brazing filler metal with a multi-element composition, and preparing foil-shaped brazing filler metal using a twin-roll casting method followed by stress-relief annealing, the problems of limited cobalt-based brazing filler metal types and brittle phase precipitation at the interface were solved. This improved the mechanical properties of brazed joints of the single-crystal high-temperature alloy DD10, meeting the connection requirements of high-pressure turbine blades for aero-engines.
Patent Information
- Application Number
- CN202511461886.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-14
AI Technical Summary
There are few types of existing cobalt-based brazing filler metals and their composition is limited. When used, they are prone to the precipitation of brittle phases at the interface, which makes it difficult to meet the high strength and toughness requirements of the single-crystal superalloy DD10.
Design a cobalt-based brazing filler metal containing 10%-12% Ni, 6%-8% Cr, 5%-7% Al, 5%-6% Ta, 3%-5% Ti, 2%-5% Pt, 2%-4% Ga, 2%-3% Re, 2%-3% V, 1%-2% Ir, 1%-2% In, 1%-2% Mn, 0.5%-1% Y, 0.5%-0.9% C, 0.1%-0.25% Ce, with the balance being Co. Prepare foil-shaped brazing filler metal using a twin-roll casting method and perform stress-relief annealing for brazing single-crystal superalloy DD10.
The mechanical properties of the brazed joints have been improved, the wettability and filling ability of the brazing filler metal and the base material have been enhanced, and the joint structure has been optimized to meet the production requirements of high-pressure turbine blades for next-generation aero-engines.
Smart Images

Figure CN120920963A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nickel-based superalloy brazing, specifically to cobalt-based brazing filler metal for brazing single-crystal superalloy DD10, its preparation method, and brazing method. Background Technology
[0002] The next generation of aero-engines is developing towards higher thrust-to-weight ratios, and to achieve this goal, the requirements for high-pressure turbine blade materials are becoming increasingly stringent. Single-crystal superalloys, by eliminating grain boundaries through their single-crystal structure, avoid the high-temperature failure caused by grain boundary weakening in traditional polycrystalline alloys. They possess excellent high-temperature strength and creep resistance, making them the preferred material for high-pressure turbine blades. Among the welding methods for this material, laser welding and electron beam welding require high assembly precision and are prone to incomplete fusion. Diffusion welding has a long process cycle and low production efficiency. Friction welding is only suitable for simple components and has poor welding effect on complex parts such as high-pressure turbine blades. Brazing, on the other hand, has a low heat input, avoids the polycrystalline formation of single-crystal superalloys at high temperatures, and the molten brazing filler metal has excellent filling ability for complex structures, making it an ideal method for joining single-crystal superalloy DD10.
[0003] Compared to nickel-based brazing filler metals, cobalt-based filler metals offer higher high-temperature strength and superior corrosion resistance, making them more suitable for joining high-pressure turbine blades operating under high temperatures and variable loads. However, the variety of cobalt-based filler metals currently available on the market is limited, and their composition is relatively simple. Furthermore, the use of cobalt-based filler metals for brazing can lead to the precipitation of brittle phases at the interface. Therefore, designing a cobalt-based filler metal for brazing the single-crystal superalloy DD10 has become a critical issue. Summary of the Invention
[0004] To address the shortcomings in the prior art, this invention improves the microstructure of the brazed joint of DD10 monocrystalline superalloy by redesigning the brazing filler metal composition, thereby enhancing the mechanical properties of the joint and providing technical support for the high-strength and high-toughness connection of DD10 monocrystalline superalloy.
[0005] To achieve the above objectives, the first aspect of the present invention provides a cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10. The cobalt-based brazing filler metal is composed of the following elemental atomic ratios: Ni 10%-12%, Cr 6%-8%, Al 5%-7%, Ta 5%-6%, Ti 3%-5%, Pt 2%-5%, Ga 2%-4%, Re 2%-3%, V 2%-3%, Ir 1%-2%, In 1%-2%, Mn 1%-2%, Y 0.5%-1%, C 0.5%-0.9%, Ce 0.1%-0.25%, with the balance being Co, and the elemental purity is greater than 99.99 wt.%.
[0006] A second aspect of the present invention provides a method for preparing a cobalt-based brazing filler metal for brazing a single-crystal high-temperature alloy DD10, the method comprising the following steps: Step 1: Weigh out Co, Ni, Cr, Al, Ta, Ti, Pt, Ga, Re, V, Ir, In, Mn, Y, C, and Ce powders according to the element atomic ratio of the cobalt-based solder, wash them, mix them, and then dry them to obtain a mixed powder; Step 2: Prepare foil-shaped brazing filler metal from the mixed powder using a twin-roll casting method; Step 3: The foil-shaped solder is subjected to stress-relief annealing, followed by secondary cleaning and drying to obtain the cobalt-based solder.
[0007] Preferably, the cleaning process in step one involves cleaning the powder surface with acetone, and the drying process involves drying in a vacuum drying oven at 80°C for 30 minutes.
[0008] Preferably, the process of preparing foil-shaped brazing filler metal by twin-roll casting in step two is as follows: first, the mixed powder is melted by induction melting under vacuum and argon atmosphere to obtain a melt; then, the melt is pushed into the roll gap using a bottom-pouring tundish to obtain the foil-shaped brazing filler metal.
[0009] Preferably, the roller gap is 0.05 mm-0.07 mm, the roller speed is 1500 rpm-2500 rpm, and the thickness of the foil-shaped brazing filler metal is 50 μm-70 μm.
[0010] Preferably, the stress-relief annealing in step three is performed at a temperature of 625°C for 90 minutes, followed by furnace cooling at a rate of ≤40°C / h. During the secondary cleaning process, the equipment is first ultrasonically cleaned with anhydrous ethanol for 20 minutes, and then cleaned with deionized water. The drying process involves drying in a vacuum drying oven at 70°C for 20 minutes.
[0011] The third aspect of this invention proposes a brazing method for single-crystal high-temperature alloy DD10, wherein the cobalt-based brazing filler metal is placed between two pretreated single-crystal high-temperature alloy DD10 base materials, and then placed together in a vacuum brazing furnace for brazing.
[0012] Preferably, during the pretreatment process, the single-crystal high-temperature alloy DD10 base material is sequentially polished using wet sandpaper with mesh sizes of 160#, 240#, 400#, 600#, 800#, 1000#, 1500#, and 2000# and a silica polishing slurry with a particle size of 150nm. After the polishing process, the single-crystal high-temperature alloy DD10 base material is ultrasonically cleaned in anhydrous ethanol for 15 minutes, then rinsed with deionized water, and finally cleaned with anhydrous ethanol and dried with a nitrogen gun to obtain the pretreated single-crystal high-temperature alloy DD10 base material.
[0013] Preferably, the brazing adopts a segmented heating and pressurization method, specifically as follows: In the first segment, the temperature is increased from room temperature to 400°C at a heating rate of 10°C / min, and held at 400°C for 10 min; in the second segment, the temperature is increased from 400°C to 800°C at a heating rate of 10°C / min, and held at 800°C for 10 min; in the third segment, the temperature is increased from 800°C to 1100°C at a heating rate of 10°C / min, and held at 1100°C for 10 min; in the fourth segment, the temperature is increased from 1100°C to a welding temperature of 1250°C at a heating rate of 10°C / min; in the fifth segment, the temperature is held at 1250°C for 150 min, with a pressure of 1.5 MPa applied throughout the process. After brazing, the furnace is cooled to room temperature.
[0014] Preferably, the vacuum degree of the vacuum brazing furnace is... .
[0015] Compared with the prior art, the present invention has the following beneficial effects: The cobalt-based brazing filler metal for connecting single-crystal high-temperature alloy DD10 proposed in this invention optimizes the microstructure and properties of the brazed joint by adding multiple elements, compared to traditional cobalt-based brazing filler metals. Ni is used to improve the compatibility between the brazing filler metal and the DD10 base material, reduce the interfacial tension between Ni-based and Co-based materials, and promote the interdiffusion of joint elements; Cr dominates the thermal strength and corrosion resistance of the joint, and at high temperatures, it preferentially forms a dense Cr2O3 oxide film, hindering the diffusion of corrosive media such as O and S into the interior; Al and Ti are the main elements for forming the γ' strengthening phase, which precipitates uniformly inside the brazed joint to improve mechanical properties; Ta is dissolved into the matrix to achieve solid solution strengthening, and can also combine with C to form TaC carbides, playing a role in dispersion strengthening; Re is used to improve the creep performance of the base material, and can also suppress the coarsening phenomenon that may occur in the γ' strengthening phase at high temperatures; V has a strong affinity for elements such as C and B, and will preferentially combine with them to form fine V C and VB particles pin dislocations and grain boundaries, hindering crack propagation; Ga, In, and Mn replace the melting point-reducing elements B and Si in traditional solders, lowering the solder's melting point while improving the wettability between the solder and the base metal, thus enhancing filling capacity; Pt and Ir, both platinum group metals, enhance joint stability under extreme conditions. Pt increases the activity of Al and Cr in the solder, promoting the rapid formation of a protective oxide film, while Ir has strong resistance to high-temperature combustion gas erosion and can inhibit the formation of sulfides on the solder surface; Y and Ce, both rare earth metals, reduce impurity segregation at grain boundaries through rare earth purification; Ce refines the size of the γ' strengthening phase and TiC and TaC carbides, while also promoting the adhesion of the protective oxide film.
[0016] The cobalt-based brazing filler metal proposed in this invention is used to connect single-crystal superalloy DD10. Compared with traditional cobalt-based brazing filler metals, it has better wettability with the base material. Furthermore, the joint microstructure is optimized through mechanisms such as solid solution strengthening, grain boundary strengthening, precipitation strengthening, and dispersion strengthening, thereby improving the mechanical properties of the joint and meeting the production requirements of high-pressure turbine blades for next-generation aero-engines. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings of the embodiments will be briefly described below. It should be understood that the drawings described below only relate to some embodiments of the present invention and are not intended to limit the present invention, wherein: Figure 1 This is a SEM microstructure image of the single-crystal high-temperature alloy DD10 connector provided in Embodiment 1 of the present invention.
[0018] Figure 2 This is a SEM microstructure of the DD10 single-crystal high-temperature alloy connector in Comparative Example 1 of this invention. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are also within the scope of protection of this disclosure.
[0020] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this subject matter pertains. It will be further understood that terms such as those defined in commonly used dictionaries shall be interpreted as having the meaning consistent with their meaning in the context of the specification and in the relevant art, and shall not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein.
[0021] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of the phrase "embodiment" in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0022] This invention provides a cobalt-based solder for connecting single-crystal high-temperature alloy DD10, specifically composed of the following elemental atomic ratios: Ni 10%-12%, for example, 10%, 11%, 12%; Cr 6%-8%, for example, 6%, 7%, 8%; Al 5%-7%, for example, 5%, 6%, 7%; Ta 5%-6%, for example, 5%, 6%; Ti 3%-5%, for example, 3%, 4%, 5%; Pt 2%-5%, for example, 2%, 3%, 4%, 5%; Ga 2%-4%, for example, 2%, 3%, 4%; Re 2%-3%, for example, 2%, 2.5%, 3%; V 2%-3%, for example, 2%, 2.5%, 3%; Ir 1%-2%, for example, 1%, 1.5%, 2%; In 1%-2%, for example, 1%, 1.5%, 2%; Mn 1%-2%, for example, 1%, 1.5%, 2%; Y 0.5%-1%, for example, 0.5%, 0.6%, 0.7%, 1%; C 0.5%-0.9%, for example, 0.5%, 0.6%, 0.7%, 0.9%; Ce 0.1%-0.25%, for example, 0.1%, 0.15%, 0.25%; the balance is Co.
[0023] The preparation process of the above cobalt-based solder is as follows: Step 1: Weigh out Co, Ni, Cr, Al, Ta, Ti, Pt, Ga, Re, V, Ir, In, Mn, Y, C, and Ce powders according to the element atomic ratio of the cobalt-based solder, and clean the powder surface with acetone to remove oil stains. After mixing, dry the powder in a vacuum drying oven at 80°C for 30 minutes to obtain mixed powder. Step 2: Prepare foil-shaped brazing filler metal from the mixed powder using a twin-roll casting method; first, melt the mixed powder using induction melting under vacuum and argon atmosphere. During the melting process, the vacuum level needs to be maintained at a certain level in the early stages. The following steps are used to remove air from the furnace. After the vacuum level stabilizes for 10 minutes, high-purity argon gas is introduced to atmospheric pressure to suppress the volatilization of low-melting-point elements Ga and In. The melting temperature is 1550℃. Electromagnetic stirring is required throughout the melting process, and the temperature is maintained for 20 minutes. After melting, the melt is pushed into the roller gap using a bottom-pouring tundish to obtain foil-shaped brazing filler metal. The roller gap is preferably 0.05 μm-0.07 mm, for example, 0.05 mm, 0.06 mm, or 0.07 mm. The roller speed is preferably 1500 rpm-2500 rpm, for example, 1500 rpm, 1800 rpm, 2000 rpm, or 2500 rpm. The thickness of the foil-shaped brazing filler metal is preferably 50 μm-70 μm, for example, 50 μm, 60 μm, or 70 μm. Step 3: Perform stress-relief annealing on the foil-shaped brazing filler metal. The entire annealing process requires vacuum protection. The annealing temperature is 625℃, and the annealing time is 90 minutes. After annealing, cool the filler metal in the furnace at a controlled rate. To prevent stress from recurring, the foil-shaped brazing filler metal is removed after the furnace temperature is ≤100℃. The removed foil-shaped brazing filler metal undergoes a second cleaning and drying process. During the second cleaning process, it is first ultrasonically cleaned with anhydrous ethanol for 20 minutes, then cleaned with deionized water, and finally dried in a vacuum drying oven at 70℃ for 20 minutes to obtain cobalt-based brazing filler metal.
[0024] The process of brazing single-crystal superalloy DD10 using the cobalt-based brazing filler metal prepared in this invention is as follows: First, the DD10 monocrystalline high-temperature alloy base material was sequentially polished using water sandpaper with mesh sizes of 160#, 240#, 400#, 600#, 800#, 1000#, 1500#, and 2000#, and a silica polishing slurry with a particle size of 150 nm. After polishing, the DD10 monocrystalline high-temperature alloy base material was ultrasonically cleaned in anhydrous ethanol for 15 min, rinsed with deionized water, and finally cleaned with anhydrous ethanol and dried with a high-purity nitrogen gun to obtain the pretreated DD10 monocrystalline high-temperature alloy base material. Then, the prepared cobalt-based brazing filler metal was placed between the upper and lower layers of the DD10 monocrystalline high-temperature alloy base material and brazed together in a vacuum brazing furnace.
[0025] The specific brazing process is as follows: A segmented heating and pressurization method is used. In the first segment, the temperature is increased from room temperature to 400℃ at a rate of 10℃ / min, and held at 400℃ for 10 min. In the second segment, the temperature is increased from 400℃ to 800℃ at a rate of 10℃ / min, and held at 800℃ for 10 min. In the third segment, the temperature is increased from 800℃ to 1100℃ at a rate of 10℃ / min, and held at 1100℃ for 10 min. In the fourth segment, the temperature is increased from 1100℃ to the welding temperature of 1250℃ at a rate of 10℃ / min. In the fifth segment, the temperature is held at 1250℃ for 150 min. A pressure of 1.5 MPa is applied throughout the process. The vacuum brazing furnace has a vacuum level of [missing information]. After brazing, the furnace is cooled to room temperature.
[0026] The cobalt-based brazing filler metal prepared according to this invention is used to braze single-crystal superalloy DD10. The roles of each element in the filler metal are as follows: Ni is used to improve the compatibility between the filler metal and the DD10 base metal, reduce the interfacial tension between Ni-based and Co-based materials, and promote the interdiffusion of joint elements; Cr dominates the thermal strength and corrosion resistance of the joint, and at high temperatures, it preferentially forms a dense Cr2O3 oxide film, hindering the diffusion of corrosive media such as O and S into the interior; Al and Ti are the main elements for forming the γ' strengthening phase, which precipitates uniformly inside the brazing seam to improve mechanical properties. Ti combines with C to form fine and dispersed carbides TiC; Ta is dissolved into the matrix to achieve solid solution strengthening, and can also combine with C to form TaC carbides, which together with TiC play a role in dispersion strengthening; Re is used to improve the creep performance of the base metal, and can also suppress the coarsening phenomenon that may occur in the γ' strengthening phase at high temperatures; V has strong affinity for elements such as C and B. Affinity preferentially binds to form fine VC and VB particles, pinning dislocations and grain boundaries, hindering crack propagation. In addition, the addition of V can stabilize the melting point of the solder. Ga, In, and Mn replace the melting point-reducing elements B and Si in traditional solders, lowering the solder melting point while improving the wettability between the solder and the base metal, and enhancing the filling capacity. Pt and Ir, both platinum group metals, play a role in enhancing the stability of the joint under extreme conditions. Pt can increase the activity of Al and Cr in the solder, promoting the rapid formation of the protective oxide film, and can also form solid solutions with Co and Ni. Ir has strong resistance to high-temperature combustion gas erosion and can inhibit the formation of sulfides on the solder surface. Y and Ce are both rare earth metals. Y reduces the segregation of impurities at grain boundaries through the rare earth purification effect. Ce can refine the size of the γ' strengthening phase and TiC and TaC carbides, while promoting the adhesion of the protective oxide film.
[0027] The present invention will be further described below through specific embodiments.
[0028] Example 1 In this embodiment, a cobalt-based solder with an atomic ratio of Co 49.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze the single-crystal superalloy DD10. The specific process is as follows: Step 1: Calculate and weigh the powders Co, Ni, Cr, Al, Ta, Ti, Pt, Ga, Re, V, Ir, In, Mn, Y, C, and Ce in an inert gas chamber according to the atomic ratio of the constituent elements of the cobalt-based solder mentioned above. Then, clean the powder surface with acetone to remove oil stains. Finally, mix and dry in a vacuum drying oven at 80°C for 30 minutes.
[0029] Step 2: The obtained mixed powder is smelted using induction melting. During the smelting process, the smelting temperature is set to 1550℃. Electromagnetic stirring is applied throughout the smelting process, and the temperature is maintained for 20 minutes. After smelting, a bottom-pouring tundish is used to push the melt into the roll gap. The roll gap is set to 0.05 mm, and the roll speed is set to 2500 rpm to obtain a foil-shaped brazing filler metal with a thickness of 50 μm.
[0030] Step 3: The prepared foil-shaped brazing filler metal is subjected to stress-relief annealing at a temperature of 625℃ for 90 min. After annealing, it is cooled in the furnace at a rate of ≤40℃ / h to prevent stress from recurring. Once the furnace temperature is ≤100℃, the foil-shaped brazing filler metal is removed and subjected to secondary cleaning and drying. During the secondary cleaning process, it is first ultrasonically cleaned with anhydrous ethanol for 20 min, then cleaned with deionized water, and finally dried in a vacuum drying oven at 70℃ for 20 min to obtain cobalt-based brazing filler metal.
[0031] Step 4: The DD10 monocrystalline high-temperature alloy base material is sequentially polished using water sandpaper with mesh sizes of 160#, 240#, 400#, 600#, 800#, 1000#, 1500#, and 2000#, and a silica polishing slurry with a particle size of 150 nm. After polishing, the DD10 monocrystalline high-temperature alloy base material is ultrasonically cleaned in anhydrous ethanol for 15 min, then rinsed with deionized water, and finally cleaned with anhydrous ethanol and dried with a high-purity nitrogen gun to obtain the pretreated DD10 monocrystalline high-temperature alloy base material. Subsequently, the prepared cobalt-based brazing filler metal is placed between the upper and lower layers of the DD10 monocrystalline high-temperature alloy base material and brazed together in a vacuum brazing furnace. The specific brazing process is as follows: First, the temperature is increased from room temperature to 400℃ at a rate of 10℃ / min, and held at 400℃ for 10 min. Second, the temperature is increased from 400℃ to 800℃ at a rate of 10℃ / min, and held at 800℃ for 10 min. Third, the temperature is increased from 800℃ to 1100℃ at a rate of 10℃ / min, and held at 1100℃ for 10 min. Fourth, the temperature is increased from 1100℃ to the welding temperature of 1250℃ at a rate of 10℃ / min. Fifth, the temperature is held at 1250℃ for 150 min. A pressure of 1.5 MPa is applied throughout the process. The vacuum brazing furnace has a vacuum degree of [missing information]. After brazing, the furnace is cooled to room temperature.
[0032] The SEM microstructure of the joint obtained after brazing is as follows: Figure 1 As shown, the joint achieves isothermal solidification, the weld is clean, and the appearance of brittle phases is avoided. The brazed joint prepared in this embodiment was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to reach 821.30 MPa.
[0033] Example 2 In this embodiment, a cobalt-based solder with an atomic ratio of Co 49.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze the single-crystal superalloy DD10. The specific process is as follows: Step 1: Calculate and weigh the powders Co, Ni, Cr, Al, Ta, Ti, Pt, Ga, Re, V, Ir, In, Mn, Y, C, and Ce in an inert gas chamber according to the atomic ratio of the constituent elements of the cobalt-based solder mentioned above. Then, clean the powder surface with acetone to remove oil stains. Finally, mix and dry in a vacuum drying oven at 80°C for 30 minutes.
[0034] Step 2: The obtained mixed powder is smelted using induction melting. During the smelting process, the smelting temperature is set to 1550℃. Electromagnetic stirring is applied throughout the smelting process, and the temperature is maintained for 20 minutes. After smelting, a bottom-pouring tundish is used to push the melt into the roll gap. The roll gap is set to 0.06 mm, and the roll speed is set to 2000 rpm to obtain a foil-shaped brazing filler metal with a thickness of 60 μm.
[0035] Step 3: The prepared foil-shaped brazing filler metal is subjected to stress-relief annealing at a temperature of 625℃ for 90 min. After annealing, it is cooled in the furnace at a rate of ≤40℃ / h to prevent stress from recurring. Once the furnace temperature is ≤100℃, the foil-shaped brazing filler metal is removed and subjected to secondary cleaning and drying. During the secondary cleaning process, it is first ultrasonically cleaned with anhydrous ethanol for 20 min, then cleaned with deionized water, and finally dried in a vacuum drying oven at 70℃ for 20 min to obtain cobalt-based brazing filler metal.
[0036] Step 4: The DD10 monocrystalline high-temperature alloy base material is sequentially polished using water sandpaper with mesh sizes of 160#, 240#, 400#, 600#, 800#, 1000#, 1500#, and 2000#, and a silica polishing slurry with a particle size of 150 nm. After polishing, the DD10 monocrystalline high-temperature alloy base material is ultrasonically cleaned in anhydrous ethanol for 15 min, then rinsed with deionized water, and finally cleaned with anhydrous ethanol and dried with a high-purity nitrogen gun to obtain the pretreated DD10 monocrystalline high-temperature alloy base material. Subsequently, the prepared cobalt-based brazing filler metal is placed between the upper and lower layers of the DD10 monocrystalline high-temperature alloy base material and brazed together in a vacuum brazing furnace. The specific brazing process is as follows: First, the temperature is increased from room temperature to 400℃ at a rate of 10℃ / min, and held at 400℃ for 10 min. Second, the temperature is increased from 400℃ to 800℃ at a rate of 10℃ / min, and held at 800℃ for 10 min. Third, the temperature is increased from 800℃ to 1100℃ at a rate of 10℃ / min, and held at 1100℃ for 10 min. Fourth, the temperature is increased from 1100℃ to the welding temperature of 1250℃ at a rate of 10℃ / min. Fifth, the temperature is held at 1250℃ for 150 min. A pressure of 1.5 MPa is applied throughout the process. The vacuum brazing furnace has a vacuum degree of [missing information]. After brazing, the furnace is cooled to room temperature.
[0037] The brazed joint prepared in this embodiment was subjected to mechanical property testing using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be 802.56 MPa.
[0038] Example 3 In this embodiment, a cobalt-based solder with an atomic ratio of Co 49.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze the single-crystal superalloy DD10. The specific process is as follows: Step 1: Calculate and weigh the powders Co, Ni, Cr, Al, Ta, Ti, Pt, Ga, Re, V, Ir, In, Mn, Y, C, and Ce in an inert gas chamber according to the atomic ratio of the constituent elements of the cobalt-based solder mentioned above. Then, clean the powder surface with acetone to remove oil stains. Finally, mix and dry in a vacuum drying oven at 80°C for 30 minutes.
[0039] Step 2: The obtained mixed powder is smelted using induction melting. During the smelting process, the smelting temperature is set to 1550℃. Electromagnetic stirring is applied throughout the smelting process, and the temperature is maintained for 20 minutes. After smelting, a bottom-pouring tundish is used to push the melt into the roll gap. The roll gap is set to 0.07 mm, and the roll speed is set to 1500 rpm to obtain a foil-shaped brazing filler metal with a thickness of 70 μm.
[0040] Step 3: The prepared foil-shaped brazing filler metal is subjected to stress-relief annealing at a temperature of 625℃ for 90 min. After annealing, it is cooled in the furnace at a rate of ≤40℃ / h to prevent stress from recurring. Once the furnace temperature is ≤100℃, the foil-shaped brazing filler metal is removed and subjected to secondary cleaning and drying. During the secondary cleaning process, it is first ultrasonically cleaned with anhydrous ethanol for 20 min, then cleaned with deionized water, and finally dried in a vacuum drying oven at 70℃ for 20 min to obtain cobalt-based brazing filler metal.
[0041] Step 4: The DD10 monocrystalline high-temperature alloy base material is sequentially polished using water sandpaper with mesh sizes of 160#, 240#, 400#, 600#, 800#, 1000#, 1500#, and 2000#, and a silica polishing slurry with a particle size of 150 nm. After polishing, the DD10 monocrystalline high-temperature alloy base material is ultrasonically cleaned in anhydrous ethanol for 15 min, then rinsed with deionized water, and finally cleaned with anhydrous ethanol and dried with a high-purity nitrogen gun to obtain the pretreated DD10 monocrystalline high-temperature alloy base material. Subsequently, the prepared cobalt-based brazing filler metal is placed between the upper and lower layers of the DD10 monocrystalline high-temperature alloy base material and brazed together in a vacuum brazing furnace. The specific brazing process is as follows: First, the temperature is increased from room temperature to 400℃ at a rate of 10℃ / min, and held at 400℃ for 10 min. Second, the temperature is increased from 400℃ to 800℃ at a rate of 10℃ / min, and held at 800℃ for 10 min. Third, the temperature is increased from 800℃ to 1100℃ at a rate of 10℃ / min, and held at 1100℃ for 10 min. Fourth, the temperature is increased from 1100℃ to the welding temperature of 1250℃ at a rate of 10℃ / min. Fifth, the temperature is held at 1250℃ for 150 min. A pressure of 1.5 MPa is applied throughout the process. The vacuum degree of the vacuum brazing furnace is... After brazing, the furnace is cooled to room temperature.
[0042] The brazed joint prepared in this embodiment was subjected to mechanical property testing using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be 784.12 MPa.
[0043] Comparative Example 1 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 55.5%, Cr 20%, Ni 13%, W 6%, Si 3%, B 1%, C 0.5%, and Fe 1% was used to braze a single-crystal superalloy DD10. The prepared cobalt-based brazing filler metal was 50 μm thick. The remaining steps were the same as in Example 1. The SEM microstructure of the joint after brazing is shown below. Figure 2 As shown, the mechanical properties of the joint were tested using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be 717.91 MPa.
[0044] This comparative example has a composition close to that of traditional cobalt-based solders. Compared to Example 1, it contains more Cr and W, and the melting point reducing elements are the traditional B and Si, such as... Figure 2 The SEM microstructure of the joint shown reveals the presence of gray, blocky borate phases in the central region of the weld. Compared to Example 1, the mechanical properties of the joint are significantly reduced.
[0045] Comparative Example 2 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 51.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze a single-crystal superalloy DD10. The thickness of the prepared cobalt-based brazing filler metal was 50 μm. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be 770.23 MPa.
[0046] Compared with Example 1, this comparative example does not contain V, and the resulting brazed joint does not contain the dispersed strengthening phases VC and VB, resulting in a decrease in mechanical properties.
[0047] Comparative Example 3 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 55.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze a single-crystal superalloy DD10. The prepared cobalt-based brazing filler metal was 50 μm thick. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be only 536.98 MPa.
[0048] Compared with Example 1, this comparative example does not contain the melting point reducing elements In and Mn, resulting in decreased solder wettability and fluidity, poorer gap filling ability, a sharp decrease in joint shear strength, and a significant decline in the mechanical properties of the joint.
[0049] Comparative Example 4 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 57%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Mn 0.5%, In 0.5%, Ga 1.5%, Pt 3%, Re 3%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze a single-crystal superalloy DD10. The prepared cobalt-based brazing filler metal was 50 μm thick. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be only 683.27 MPa.
[0050] Compared with Example 1, the contents of the reducing elements In, Ga, and Mn in this comparative example are all lower than the ranges set in this invention, resulting in a decrease in the fluidity and wettability of the solder and a decrease in shear strength.
[0051] Comparative Example 5 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 49.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 1%, and C 0.5% was used to braze a single-crystal superalloy DD10. The thickness of the prepared cobalt-based brazing filler metal was 50 μm. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be only 720.16 MPa.
[0052] Compared with Example 1, this comparative example does not contain the rare earth element Ce, but increases the content of the rare earth element Y, which weakens the dispersion strengthening effect of γ' and carbides and reduces the shear strength.
[0053] Comparative Example 6 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 52.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze a single-crystal superalloy DD10. The prepared cobalt-based brazing filler metal was 50 μm thick. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be only 704.71 MPa.
[0054] Compared with Example 1, this comparative example does not contain Re, which causes some of the γ' reinforcing phase to coarsen at high temperatures, reducing the mechanical properties of the joint.
[0055] Comparative Example 7 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 49.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze a single-crystal superalloy DD10. The prepared cobalt-based brazing filler metal was 40 μm thick. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be 691.85 MPa.
[0056] Compared with Example 1, the thickness of the brazing filler metal prepared in this comparative example is smaller than the range set by the present invention, the filling capacity of the brazing filler metal is limited, some areas are not welded, and the mechanical properties of the joint are reduced.
[0057] Comparative Example 8 In this comparative example, a cobalt-based brazing filler metal with an atomic ratio of Co 49.5%, Ni 10%, Cr 7%, Al 6%, Ta 5%, Ti 4%, Ga 4%, Pt 3%, Re 3%, V 2%, In 2%, Mn 2%, Ir 1%, Y 0.75%, C 0.5%, and Ce 0.25% was used to braze a single-crystal superalloy DD10. The prepared cobalt-based brazing filler metal was 80 μm thick. The remaining steps were the same as in Example 1. The joint was tested for mechanical properties using an INSTRON 3382 electronic universal testing machine, and the shear strength was found to be 628.01 MPa.
[0058] Compared with Example 1, the thickness of the brazing filler metal prepared in this comparative example exceeds the range set by the present invention. The diffusion of elements inside the brazing filler metal is incomplete, forming brittle phases and stress concentration areas, resulting in a decrease in the mechanical properties of the joint.
[0059] The embodiments given above are preferred examples for implementing the present invention, and the present invention is not limited to the above embodiments. Any non-essential additions or substitutions made by those skilled in the art based on the technical features of the present invention are within the protection scope of the present invention.
Claims
1. A cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10, characterized in that, The cobalt-based solder is composed of the following elemental atomic ratios: Ni 10%-12%, Cr 6%-8%, Al 5%-7%, Ta 5%-6%, Ti 3%-5%, Pt 2%-5%, Ga 2%-4%, Re 2%-3%, V 2%-3%, Ir 1%-2%, In 1%-2%, Mn 1%-2%, Y 0.5%-1%, C 0.5%-0.9%, Ce 0.1%-0.25%, with the balance being Co, and the elemental purity is greater than 99.99 wt.%.
2. The method for preparing a cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10 according to claim 1, characterized in that, The preparation method of the cobalt-based solder includes the following steps: Step 1: Weigh out Co, Ni, Cr, Al, Ta, Ti, Pt, Ga, Re, V, Ir, In, Mn, Y, C, and Ce powders according to the element atomic ratio of the cobalt-based solder, wash them, mix them, and then dry them to obtain a mixed powder; Step 2: Prepare foil-shaped brazing filler metal from the mixed powder using a twin-roll casting method; Step 3: The foil-shaped solder is subjected to stress-relief annealing, followed by secondary cleaning and drying to obtain the cobalt-based solder.
3. The method for preparing a cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10 according to claim 2, characterized in that, The cleaning process described in step one involves cleaning the powder surface with acetone, and the drying process involves drying in a vacuum drying oven at a temperature of 80°C for 30 minutes.
4. The method for preparing a cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10 according to claim 2, characterized in that, The process of preparing foil-shaped brazing filler metal using the twin-roll casting method described in step two is as follows: First, the mixed powder is melted in a vacuum and argon atmosphere using induction melting to obtain a melt. Then, the melt is pushed into the roll gap using a bottom-pouring tundish to obtain the foil-shaped brazing filler metal.
5. The method for preparing a cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10 according to claim 4, characterized in that, The roller gap is 0.05 mm-0.07 mm, the roller speed is 1500 rpm-2500 rpm, and the thickness of the foil-shaped brazing filler metal is 50 μm-70 μm.
6. The method for preparing a cobalt-based brazing filler metal for brazing single-crystal high-temperature alloy DD10 according to claim 2, characterized in that, The stress-relief annealing in step three is performed at a temperature of 625℃ for 90 min. After annealing, the furnace is cooled at a rate of ≤40℃ / h. During the secondary cleaning process, the furnace is first ultrasonically cleaned with anhydrous ethanol for 20 min, followed by cleaning with deionized water. The drying process involves drying in a vacuum drying oven at 70℃ for 20 min.
7. A brazing method for a single-crystal high-temperature alloy DD10, characterized in that, The cobalt-based brazing filler metal described in claim 1 is placed between two pretreated single-crystal high-temperature alloy DD10 base materials, and then placed together in a vacuum brazing furnace for brazing.
8. The brazing method for a single-crystal high-temperature alloy DD10 according to claim 7, characterized in that, During the pretreatment process, the DD10 monocrystalline high-temperature alloy base material is sequentially polished using wet sandpaper with mesh sizes of 160#, 240#, 400#, 600#, 800#, 1000#, 1500#, and 2000#, and a silica polishing slurry with a particle size of 150nm. After polishing, the DD10 monocrystalline high-temperature alloy base material is ultrasonically cleaned in anhydrous ethanol for 15 minutes, then rinsed with deionized water, and finally cleaned with anhydrous ethanol and dried with a nitrogen gun to obtain the pretreated DD10 monocrystalline high-temperature alloy base material.
9. The brazing method for a single-crystal high-temperature alloy DD10 according to claim 7, characterized in that, The brazing process employs a segmented heating and pressurization method, specifically as follows: In the first segment, the temperature is increased from room temperature to 400℃ at a rate of 10℃ / min, and held at 400℃ for 10 minutes; in the second segment, the temperature is increased from 400℃ to 800℃ at a rate of 10℃ / min, and held at 800℃ for 10 minutes; in the third segment, the temperature is increased from 800℃ to 1100℃ at a rate of 10℃ / min, and held at 1100℃ for 10 minutes; in the fourth segment, the temperature is increased from 1100℃ to a welding temperature of 1250℃ at a rate of 10℃ / min; and in the fifth segment, the temperature is held at 1250℃ for 150 minutes, with a pressure of 1.5 MPa applied throughout the process. After brazing, the furnace is cooled to room temperature.
10. The brazing method for a single-crystal high-temperature alloy DD10 according to claim 9, characterized in that, The vacuum level of the vacuum brazing furnace .
Citation Information
Patent Citations
Method for brazed connection of DD98M single-crystal high-temperature alloy by Pd-Si composite solder
CN108188520A
Cobalt-based powder brazing filler metal for high-temperature alloy connecting as well as preparation method and application of cobalt-based powder brazing filler metal
CN109909641A
High-temperature cobalt base brazing filler metal and application thereof
CN110497117A
Nickel-cobalt-based high-temperature alloy welding rod for 800 DEG C-grade ultra-supercritical power station boiler
CN113399862A
High-performance brazing method for third-generation single crystal high-temperature alloy
CN113909610A